Intersectional Disruptor: A Special Educator of Color Living and Teaching in the Intersections. (February 2022) - Siuty, Molly Baustien; Atwood, Alexis
Scholars argue that teaching for disability and racial justice in education must be intersectional to jointly disrupt the marginalizing processes that occur at the nexus of ableism and racism. It has been suggested that special educators of color can play a key role in addressing inequity and disproportionality in special education. Yet, special educators of color are perpetually underrepresented in the workforce. At the same time, special education research remains overwhelmingly silent on the unique experiences and contributions of educators of color, particularly Black women. This qualitative case study employs DisCrit Classroom Ecology and Positioning Theory as a conceptual framework to explore how Sarah, a Black special educator, drew on her life histories to enact transformative teacher resistance. Implications will be offered for how special education teacher preparation programs can center the crucial role of Black educators in special education.